Neoplasm Diagnosis Coding Accuracy And Completeness: A Retrospective Review - Kuntoadi, Gama Bagus; Christin, Rumondang; Lestari, Santi; Angelina, Novia (STIKes Widya Dharma Husada Tangerang, 2025)
Medical records are essential documents that support clinical services and healthcare planning. One indicator of medical record quality is the accuracy and completeness of diagnosis codification, particularly in neoplasm cases. This study aims to determine the accuracy and completeness of neoplasm diagnosis codification at RSUP Dr. Sitanala for the period of October–December 2024. The research used a descriptive method with a quantitative and retrospective approach. The object of the study consisted of 116 inpatient and outpatient medical records with neoplasm diagnoses, while the subjects were six medical record coders. Data were collected through observation, questionnaires, and checklists. The results showed that RSUP Dr. Sitanala has implemented a codification SOP with 83.3% compliance. However, the SOP does not specifically regulate the inclusion of morphology codes for neoplasm cases. The accuracy rate of topography code assignment was 78.45% (91 accurate records), while 21.55% (25 records) were inaccurate. Additionally, all 116 records (100%) lacked morphology codes, rendering them incomplete. Regarding human resources, all coders held a formal education background in medical record and health information, yet one coder had never received coding training. Other contributing factors included limited understanding of medical terminology and the absence of specific training related to morphology coding for neoplasms.